Ecology And Population Genetics Of The Malaria Vector Anopheles Arabiensis Patton In The Republic Of Sudan - Mohamed, Mashair Sir Elkhatim Mustafa (2013)
The main objectives of this study were to update the geographical distribution of Anopheles gambiae complex and to investigate the genetic structure of Anopheles arabiensis, the main malaria vector in Sudan. A total of 4,932 mosquitoes including 3047 larvae and 1885 adults (males and females) were collected from Abu Algoni and Algerif West in Sudan during June 2010 to May 2011. Of the total mosquitoes collected, 88.9% were from Algoni and 11.1% from Algerif West. Two species, An. rufipes and An. arabiensis were encountered, the former was only found in Abu Algoni, but the latter was found in both villages, and represented more than 99% of the total collection. Mosquitoes were found breeding in many types of habitats including canals, temporary pools of water, animal hooves, water from broken pipes, and water storage containers. In both villages the seasonal abundance of An.arabiensis was highest during the rainy season; this could be associated with the availability of more breeding sites created by rainfall. The majority were parous, indicating high survival rates and thus high vectorial capacity in transmitting malaria.